O educador musical na escola regular em Belo Horizonte - Myrna Valeria Campos de Oliveira (2011)
This research, entitled "The music educator in regular schools in Belo Horizonte" aims, through interviewing, to acknowledge and analyze the practice of 5 (five) music educators who teach at regular schools in Belo Horizonte, checking the conditions of their field work. Its specific objectives are: (1) identify the characteristics and the musical training of the educators interviewed; 2) investigate the methodological practices in the different age groups which they work with; (3) determine the problems faced and the strategies they have developed to find solutions to these problems. Another important aspect of this research is the verification of public policies and legislation of the State of Minas Gerais, in relation to music education, a topic that is facing changes due to the inclusion of music content to be initiated in 2012. The research found that there is a need for a comprehensive training for music educators, that is focused on musical practice within the classroom. It is also necessary to improve the physical conditions and material resources that will be used to teach music at school. Another conclusion is that the proposed curriculum will need to be adapted according to the sociocultural context of each school, region or city. In face of all these demands, it will be necessary a joint effort of music educators, so that a physical and ideological space for music in school may be accomplished.